Law applicable to oponibility against third parties of an assignment of credits. Commentary to the Judgment of the Court of Justice of the European Union October 9, 2019 - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Article 14 of Regulation 593/2008, on the law applicable to contractual obligations “Rome I”, does not designate, directly or by analogy, the law applicable to the possibility of transferring credits to third parties in the event of multiple transfers of a credit by the same creditor to successive assigns. In this way, the Court of Justice of the European Union of October 9, 2019, Case C-548/18, responds to a request for a preliminary ruling raised in the procedure between BNP and TeamBank in relation to the judicial deposit by the bankruptcy administrator. of the debtor of the amount of certain credits of which both entities declared themselves creditors because they had been assigned.